Incidence of Four Canals in Permanent Mandibular First Molar in Patients Attending Dhulikhel Hospital. - Acharya, Nisha; Paudel, Durga; Chakradhar, Anil (Journal of College of Medical Sciences-Nepal, 2018)
Background & Objectives: The success of root canal therapy greatly depends upon the proper cleaning, shaping and three dimensional sealing. Besides these, the locations of all the canals, is mandatory to achieve the rationale of endodontic therapy. Hence, variation in root canal anatomy has clinical significance. The objective of this study was to assess the presence of four root canals in permanent mandibular first molars in patients attending Dhulikhel Hospital. Materials & Methods: The clinical and radiographic examination of one hundred and nine permanent mandibular first molars, undergoing root canal treatment was conducted. Mandibular first molar teeth of both male and female patients of all age groups were included. Results: Out of 109 samples (46.8% male and 53.2% female), three and four canals were found in 44.1% and 55.9% respectively in root treated permanent mandibular first molars. Conclusion: This study concluded that 55.9% of permanent mandibular first molars have four root canals, indicating higher incidence than that of three canals, in patients attending Dhulikhel hospital.